Effect of Plant Density on Growth, Yield and Quality of Sesame (Sesamum indicum L.) Varieties Grown in Lateritic Soils of Konkan - KADAM, P. S.; CHAVAN, M. G.; GAME, V. N. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
Field experiment was conducted on coastal lateritic soils of Konkan region to study the effect of plant density on growth and yield of sesame varieties during summer season at Agronomy Farm, Dr. Balasaheb Sawant Konkan Krishi Vidyapeeth, Dapoli. Dist. Ratnagiri. The experimentwas laid out in split plot design with three replications. The main plot treatments were four sesame varieties viz., Phule Til-1, JLT-26, JLT-408 and JLT-7. The sub plot treatments comprised three plant densities viz., 1, 66, 666 plants ha-1, 2,22,222 plants ha-1 and 3,33,333 plants ha-1. Results revealed that the growth characters of sesame variety JLT-7 were significantly higher followed by Phule Til-1, JLT-408 and JLT-26. Sesame variety JLT-7 produced significantly higher seed yield (12.5 q ha-1) and stalk yield (25.7 q ha-1) over rest of the varieties. The growth characters like plant height and number of functional leaves were significantly higher at plant density of 3,33,333 plants ha-1 as compared to other plant density treatments. The plant density of 1,66,666 plants ha-1 recorded significantly higher number of branches plant-1 and dry matter accumulation plant-1 over rest of plant densities. The plant density 1, 66,666 plants ha-1 recorded significantly higher values of most of the yield attributes. The plant density of 2,22,222 plants ha-1 produced significantly higher seed yield (12.5 q ha-1). However, stalk yield was higher at 3,33,333 plants ha-1 over rest of the plant densities. The variety JLT-7 recorded significantly higher protein and oil content (%) in seed over rest of the varieties. The plant density treatment 1,66,666 plant ha-1 significantly increased the protein content in seed as compared to rest of plant densities. Oil content in seed was not influenced due to plant densities.